Multisectoral coordination in public health: insights from the 8th EMPHNET regional conference - Rana AlHamawi; Suhaib Yehya; Faris Lami; Mahmudur Rahman; Muhammad Sartaj; Jonathan E. Suk; Scott F. Dowell; Mohammed Youbi; Heba Mahrous; Vimala Edwin; Abdul Rehman; Mohannad Al Nsour; et al. (Frontiers in Public Health)
The concept of multisectoral coordination has been comprehensively described in multiple internationally recognized frameworks. However, the institutionalization of the concept is highly complex and requires further exploration. During the 8th Biennial Regional Conference of the Eastern Mediterranean Public Health Network (EMPHNET), a roundtable session brought together a panel of global and regional experts in multisectoral coordination to share knowledge and expertise, regarding the concept of multisectoral coordination, and the implementation and formalization of coordination mechanisms within national structures, particularly in the Eastern Mediterranean Region (EMR). Discussions also addressed the challenges associated with effective multisectoral coordination, along with proposed solutions and lessons learned from past public health events. The findings of the roundtable emphasized the importance of multisectoral coordination in addressing multifaceted public health events. Multisectoral coordination was described as the “master key” for tackling complex issues at the human-animal-environmental interface. The functionality of coordination within national structures during peacetime was deemed essential for its operationality during emergencies. Therefore, panelists recommended adopting a systematic approach to emergency coordination which includes identifying sector leaders, identifying the main coordination activities, exercising plans and continuous quality improvement. Additionally, the purpose of coordination should be clearly identified and articulated alongside the shared benefits for improved engagement of relevant sectors. Several challenges to effective coordination were identified, along with corresponding solutions. These included limited operational effectiveness of coordination mechanisms during peacetime, lack of awareness regarding the importance of coordination, limited trust and co-ownership within and between organizations, and competing priorities and conflicts of interest.